A geostatistical primer - Brooker, Peter I. (World Scientific New Jersey, 1991)
This book is an introductory text on geostatistics which treats spatially distributed random data and can be applied to areas like ore reserve assessment, pollution problems, forestry applications and water resource problems. The underlying mathematical formalism of geostatistics is obscure to most geology majors who nowadays are increasingly expected to take a more quantitative approach to their discipline rather than the traditionally descriptive approach. The author has approached the teaching of geostatistics in a very pragmatic way via a two dimensional data set. Many figures illustrating concepts and results are given and mathematics is reduced to a minimum.
Keywords: Geology - Statistical methods; Stochastic processes